Introduction to green biocomposites - Golieskardi A.; Hoque M.E.; Golieskardi M. (Elsevier, 2023)
In recent years, a significant body of research has been focused on the sustainability of resources and adverse human impacts on the ecosystem. Therefore much effort has been made to potentially reprocess industrial waste and to seek a replacement for petroleum-based products with biodegradable materials. Green biocomposites are broadly recognized as composite systems with superior performance, strength and versatility, whose complete degradability of its components and composability make them comparatively attractive. Green biocomposites are generally constructed by the incorporation of a biodegradable polymeric matrix reinforced by eco-friendly and renewable fibers. These biomaterials have made an overwhelming impression on the worlds economy and found applications in diverse markets including aerospace, automobile, biomedical, etc. These products provide a viable solution to the issue of sustainability and ecological concerns surrounding plastic waste which has become the primary topic of many environmental debates. In recent years, the ecological impacts of materials and technologies seem to serve as one of the factors affecting consumers purchasing decisions. Additionally, there is constant pressure from environmental authorities on companies to closely monitor and manage the environmental effects of their products. Thereby, it is not surprising to see the industries seeking green replacement of the nondegradable and synthetic components used in their products. Besides the environmental incentive, the performance of many potential components for the prospective green composite systems has also been explored, and green materials in place of matrix and reinforcement materials have been tested to be recognized as a substitute which champions both adequate strength and stiffness besides being financially viable so as to be promising materials for the biocomposite systems. In this chapter, an overview of composites structure, history and the ecological concerns surrounding the polymer-based composites are provided. Furthermore, the use of green alternatives including natural fibers as reinforcement and biopolymers as the matrix is discussed. Lastly, some of the applications of green biocomposites, particularly biomedical applications, are outlined. 2021 Elsevier Ltd All rights reserved.